Blood supply management in times of SARS‐CoV‐2 pandemic – challenges, strategies adopted, and the lessons learned from the experience of a hospital‐based blood centre. Issue 5 (26th October 2020) - Pandey, Hem Chandra; Coshic, Poonam; C S, Chippy; Arcot, Priyadarsini Jayachandran; Kumar, Karan
Abstract : Introduction: Numerous concerns regarding maintenance of blood inventory have been raised after SARS‐CoV‐2 pandemic outbreak. These concerns were based on the experience of blood centres in previous pandemics where shortage of blood components was reported. The present study had tried to understand the impact of SARS‐CoV‐2 pandemic on blood collection and demand as well as the impact of disaster planning in maintaining an adequate inventory. Methods: Data related to blood supply and demand were collected retrospectively using blood bank management software for pre‐COVID‐19 and COVID‐19 time period and compared. Strategies adopted and effects of changes in existing disaster plans to maintain an adequate inventory were studied. Results: A drastic fall in the red cell inventory was observed as compared to pre‐COVID‐19 time period was observed due to disproportionate decrease in blood collection (1/6 to 1/9 of the previous collection) and demand (1/2 of the previous demand). The buffer stock fell gradually over a period of three weeks with cancellation of planned blood donation drives. A buffer stock equivalent to 2‐week inventory led to adequate inventory in the initial lockdown periods. Similar fall was observed in the platelet inventory with reduction in the blood collection but almost a proportionate reduction in the platelet demand led to adequate inventory. No increase in wastage was observed for both red cells and platelets during this period. Discussion: A buffer stock of blood and blood components, strict adherence to the transfusion triggers, good coordination with the clinical staff and a prospective review of blood transfusion requests to ensure rational blood transfusion were some of the steps which helped us to successfully maintain transfusion requirements in the initial phases of the COVID‐19 pandemic. Use of first‐in‐first‐out policy prevented any wastage due to outdating of blood.